Hubungan motivasi ibu hamil dengan pemberian ASI dini di Wilayah Kota Bandung - Sri Wisnu Wardani; Sriwenda Djudju; Widaningsih Neneng (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2020)
Early breastfeeding from the beginning of life is important for the survival and optimal growth and development of a baby. The continuity of the practice of early breastfeeding is influenced by several factors, including maternal motivation. Motivation is an intrinsic factor that drives behavior. It is very important to know the motivation of pregnant women to carry out early breastfeeding so that effective strategies for increasing coverage of exclusive breastfeeding can be identified. This study aims to analyze the relationship between the motivation of pregnant women with early breastfeeding in the City of Bandung. This study uses a quantitative correlational approach for 80 trimester pregnant women totaling 80 people from 4 Community Health Centers in the City of Bandung. Data collection is done by collecting primary data from filling out Motivation questionnaires and interviews to supplement the quantitative data obtained. Data were analyzed using the Chi-Square statistical test. The motivation of pregnant women to give early breastfeeding had the same subjects between good motivation and not, that is 50%. The behavior of giving early breastfeeding by respondents by 56.3% and there is a significant relationship between the motivation of pregnant women with early breastfeeding in Bandung city area with a p-value <0.001 (p nilai0.05 value). The conclusion of this study is early breastfeeding has a significant relationship with the motivation of pregnant women statistically. Suggestions from this study are to improve the facilities and support of health workers in particular as well as the family and the immediate environment as a role model so that early breastfeeding is more optimal.